(untitled) (Journal of actual problems of jurisprudence, 2026)
This article is devoted to the study of the prospects for the development of insurance law in the context of the transformation of market relations and integration processes. The purpose of the scientific research is to determine the main directions for the development of insurance law, taking into account the specific features of the development of modern market relations in the context of international integration. The article substantiates the proposition that insurance law is currently in the process of formation as a complex branch of law. To support this position, the author analyzes the characteristics that allow insurance law to be considered a complex branch of law. In addition, the paper clearly demonstrates the specific features of the application of dispositive and imperative methods of legal regulation in insurance legal relations. The relevance of the scientific research lies in the need to reconsider the prospects for the development of insurance law in the context of the transformation of modern market relations and international integration processes. Based on a comprehensive analysis of theoretical provisions and the system of current insurance legislation, priority directions for the further development of insurance law within the legal system of the Republic of Kazakhstan have been identified. Furthermore, the author conducts a comprehensive analysis of the views and concepts of various scholars, including legal scholars from the post-Soviet space who have studied the problems of the theory of insurance law. The theoretical significance of the study lies in the possibility of using the obtained results in further scientific research in the field of insurance law. The practical significance consists in the systematization of research directions in the sphere of insurance legal relations and in the improvement of the theoretical provisions of insurance law. Keywords: international integration, insurance legislation, insurance relations, insurance law, insurance activity, subject of insurance law, insurance contract.